Exploring inhibiting factors to affordable housing provision in Lagos metropolitan city, Nigeria - Ogundipe, Kunle Elizah; Owolabi, James Dele; Ogunbayo, Babatunde Fatai; Aigbavboa, Clinton Ohis (Frontiers in Built Environment, 2024)
Different inhibiting factors have affected the need for affordable housing provisions to keep pace with the increase in urbanisation and population growth, leading to the non-availability of desirable, affordable housing goals for low-income earners. Unfortunately, these inhibiting factors continue to create challenges that affect affordable housing development for low-income earners. Hence, this study examines the inhibiting factors affecting affordable housing provisions using Lagos metropolitan city, Nigeria, as a case study exemplar. The need for affordable housing provisions to keep pace with urbanisation and population growth has led to research findings for achieving desirable, affordable housing goals. ofstrategies to This study examines the inhibiting factors of affordable housing provisions in a Lagos metropolitan City, Nigeria. A quantitative research design was employed, using the survey to collect data from the target populations of low-income earners in Lagos, Nigeria, through a purposive sampling technique with a high response rate of 75.3%. Descriptive and exploratory factor analysis was conducted on the retrieved data and Cronbach's alpha test to determine data reliability and interrelatedness. Thirty-seven identified inhibiting factors of affordable housing provisions were clustered into seven components: problems with affordable land and security of tenure; socioeconomic constraints; problems with conventional materials and technologies; unpredictable inexternal factors; absence of innovative framework and supply chain; absent of community collaboration and external economic fluctuation factors; and urbanisation factors. The implications of the study findings provide a better understanding of land tenureship, improved social inclusion, community-based stakeholders stakeholder collaboration, standardisation of indigenous construction materials and technologies utilisation, and housing policy reforms to alleviate the shortage of affordable housing delivery in metropolitan cities. The study recommends successful implementations of affordable housing provisions hinged on an innovative housing framework and affordable supply chain through design, standardisation of non-conventional materials and technologies utilisation and social inclusion. The study's conclusion gives housing stakeholders, realtors, policymakers, and government agencies the ability to understand and implement strategies to overcome socioeconomic constraints, land security of tenure, and urbanisation factors to predict and improve affordable housing demand and supply in metropolitan cities.